Antibacterial activities of polymeric poly(dl-lactide-co-glycolide) nanoparticles and Soluplus® micelles against Staphylococcus epidermidis biofilm and their characterization1. Issue 88 (25th September 2015) - Takahashi, Chisato; Saito, Shoko; Suda, Asami; Ogawa, Noriko; Kawashima, Yoshiaki; Yamamoto, Hiromitsu
<x xml:space="preserve">Abstract</x> We have successfully prepared polymeric micelles based on polyvinyl caprolactam–polyvinyl acetate–polyethylene glycol graft copolymer (Soluplus®) for a drug delivery system on a biofilm.